(untitled) (Journal of Computational Mathematics, 2018)
We consider the quadrilateral Q1 isoparametric element and establish an optimal error estimate in H1 norm for the interpolation operator under a weaker mesh condition which admits anisotropic quadrilaterals and allows the quadrilateral to become a regular triangle in the sense of maximum angle condition [5,11].